X-Chromosome Markers Used in Deficiency of Paternity Case - Azzah Bahaa Abdulazeez 1,2, Ismail Hussein Aziz 1 , Mohammed Mashni Farhan 2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Cases of deficiency paternity, characterized by missing of the alleged father, are a task for forensic genetics.Recently these cases were determined using sets of extremely polymorphic autosomal short tandem repeats(STRs), which indicate to powerful likelihood ratios (LR). Some difficult cases emerge whenever the kinshiphighly remote or if the another hypotheses are not properly formulated because of the absence of information.In these situations, beyond the routinely used marker set, laboratories usually enlarge the number and/or thetype of markers analysed. A set of 14X-STRs is further advantageous than 21 autosomal STRs (AS STRs)biallelic markers. Furthermore, the utility of X-STRs was also appear in cases shows that in father–daughterduos and merely a close family member of the alleged parent (father or mother) is existing for testing. Herewe present a cases with biological daughter of the alleged father and her mothers and putative grandmotherwas the genotyped relative are available for reconstructing his haplotype . Aiming to increase the PaternityIndex (PI), Probability of Paternity (PP), and obtain more reliable results. The result of X STR showed thatthe missing person (father) share 50% genotype with the donors (daughter)and (his mother) at each locus,there are no alleles in any one of these 13 loci conflict with the alleles inherited from her father and PosteriorProbability of paternity was (99.999958%) that is mean the missing person was biological father for thisdonor daughter.